2023
DOI: 10.1155/2023/3848846
|View full text |Cite
|
Sign up to set email alerts
|

Some Further Results Using Green’s Function for s -Convexity

Abstract: For s-convex functions, the Hermite–Hadamard inequality is already well-known in convex analysis. In this regard, this work presents new inequalities associated with the left-hand side of the Hermite–Hadamard inequality for s-convexity by utilizing a novel technique based on Green’s function. Also, Hölder, Young, and power-mean inequalities are used to obtain these new inequalities. Finally, some applications to special means of real numbers are provided. In conclusion, we think that the methodology used in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Since then, researchers have obtained new identities using this inequality and special methods. Important studies about this inequality can be found in references [22][23][24][25].…”
Section: Preliminariesmentioning
confidence: 99%
“…Since then, researchers have obtained new identities using this inequality and special methods. Important studies about this inequality can be found in references [22][23][24][25].…”
Section: Preliminariesmentioning
confidence: 99%